A needs assessment of a group of at-risk youth in Mitchell's plain a discourse analytic approach - Abrahamse, Petra (University of the Western Cape, 2021)
Philosophiae Doctor - PhD === This study focused on determining and understanding the needs of a group of at-risk youth in Mitchell's Plain in order to identify the social competencies and basic life skills they require to enable them to cope with their life circumstances. The first phase of this study, which adopted a qualitative framework to identify the needs of these at-risk youth, was a review of the relevant literature. This review revealed that not only is there a need to understand the transitional stage that youth find themselves in; just as important is the necessity of being aware of the political, economic and social contexts which impact on them. Focus group interviews, which are recognised as encouraging participants to reveal more than in individual interview situations, were then used to obtain the data. Thereafter, both discourse analysis and systems theory were employed to analyse the data. Thus, not only were the utterances. of the participants subjected to rigorous linguistic analysis in order to discover the subtext of what they were saying; the researcher also took cognisance of the wide range of systems which impact on youth, from the macro socio-economic levels to the micro family and school levels. these at-risk youth began to emerge. These, in turn, highlighted those affective, cognitive and behavioural skills needed by at-risk youth to optimise their future development. The analysis of the data also served to validate the assumptions contained in the working hypotheses, namely that the youths' discourses would reveal their most dominant needs. In this respect, it became apparent that socio-economic deprivation, poor educational opportunities, problematic peer and family relationships as well as intra-community violence are all underpinning issues, which contribute to the youth being vulnerable to becoming at risk. As such, these issues require urgent addressing. Furthermore, the effects of racism in post -apartheid South Africa became evident as the youths revealed the inadequacies of their current situation. The youths' discourses, thus, highlighted the economic disparities that are highly visible within their community, despite the political transformation within South Africa. The study concludes by suggesting that if a meaningful way forward is to be found, it lies in improving our understanding of how preventative intervention can effectively take place in the structural, social and interpersonal domains to provide a national programme of action for youth.